Improving Adolescents’ Mental Health through Spiritual Motivation Training and Emotion Regulation Workshop - Sari, Ratna; Saleh, M Nurul Ikhsan (Counsellia: Jurnal Bimbingan dan Konseling, 2023)
One of the most significant effects of the Covid-19 Pandemic on adolescents is the learning system at schools or universities that switches online and the social environment limitation. The incapacity of adolescents to adapt during a pandemic can cause stress, which affects adolescents’ poor mental health. Therefore, efforts must be made to maintain adolescents’ mental health, including the provision of Spiritual Motivation Training and Emotion Regulation Workshops. The purpose of this study is to examine the effectiveness of Spiritual Motivation Training and Emotion Regulation Workshop in reducing stress levels, enhancing emotional regulation skills, and improving adolescents’ mental health. This study employs action research methods. Observation, interviews, the Stress Inventory Scale, the Emotional Regulation Questionnaire, and the Mental Health Inventory were used to collect data. This study used a mixed-methods design. The Wilcoxon Test and the theories of Miles, Huberman, and Saldana were utilized to examine the data. 11 participants in this study filled out measurement instruments before and after receiving treatment. Spiritual Motivation Training and Emotion Regulation Workshop were found to be successful in reducing respondent stress and enhancing subject understanding of the steps involved in implementing emotion regulation, but less effective in improving respondent mental health.